An Immunoassay for Dibutyl Phthalate Based on Direct Hapten Linkage to the Polystyrene Surface of Microtiter Plates - Wei, Chenxi; Ding, Shumao; You, Huihui; Zhang, Yaran; Wang, Yao; Yang, Xu; Yuan, Junlin (PLOS ONE, 2011)
Background Dibutyl phthalate (DBP) is predominantly used as a plasticizer inplastics to make them flexible. Extensive use of phthalates in both industrial processes and other consumer products has resulted in the ubiquitous presence of phthalates in the environment. In order to better determine the level of pollution in the environment and evaluate the potential adverse effects of exposure to DBP, immunoassay for DBP was developed. Methodology/Principal Findings A monoclonal antibody specific to DBP was produced from a stable hybridoma cell line generated by lymphocyte hybridoma technique. An indirect competitive enzyme-linked immunosorbent assay (icELISA) employing direct coating of hapten on polystyrene microtiter plates was established for the detection of DBP. Polystyrene surface was first oxidized by permanganate in dilute sulfuric acid to generate carboxyl groups. Then dibutyl 4-aminophthalate, which is an analogue of DBP, was covalently linked to the carboxyl groups of polystyrene surface with 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC). Compared with conjugate coated format (IC50 = 106 ng/mL), the direct hapten coated format (IC50 = 14.6 ng/mL) improved assay sensitivity after careful optimization of assay conditions. The average recovery of DBP from spiked water sample was 104.4% and the average coefficient of variation was 9.95%. Good agreement of the results obtained by the hapten coated icELISA and gas chromatography-mass spectrometry further confirmed the reliability and accuracy of the icELISA for the detection of DBP in certain plastic and cosmetic samples. Conclusions/Significance The stable and efficient hybridoma cell line obtained is an unlimited source of sensitive and specific antibody to DBP. The hapten coated format is proposed as generally applicable because the carboxyl groups on modified microtiter plate surface enables stable immobilization of aminated or hydroxylated hapten with EDC. The developed hapten coated icELISA can be used as a convenient quantitative tool for the sensitive and accurate monitoring DBP in water, plastic and cosmetic samples.